Analisis Pembinaan Iman Anak dan Remaja Menggunakan Model Evaluasi CIPP di Stasi Santo Hieronimus Pinem - Lumbanbatu, Johannes Sohirimon; Gurusinga, Rikha Emyya (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to map the implementation of children’s and adolescents’ faith formation at Saint Hieronimus Pinem Station using the CIPP (Context, Input, Process, Product) evaluation model within a qualitative descriptive approach. In this research, the CIPP model is applied as an analytical framework rather than a quantitative measurement tool. Data were collected through in-depth interviews, direct observation, and documentation to obtain a comprehensive understanding of the real conditions influencing the faith formation program. The findings show that the program still faces several challenges, including low parental involvement, the influence of digital technology, limited human resources, and traditional teaching methods. The study recommends continuous needs assessment, structured planning, and creative pastoral methods suited to the local context. The qualitative CIPP model proves effective in systematically analyzing and improving pastoral programs according to real community needs.